PROPER HEALTHY : 80 PLANT-BASED RECIPES WITH A BOOST - Harris, Calum; Hamilton, Haarala (London : Carnival, 2024)
If you're looking for a no-nonsense way to eat well, then 'Proper Healthy' has you covered. Calum Harris has done all the hard work for you, working with a registered dietician to create easy, plant-based dishes that come packed with up to four health benefits to boost your meals. Whether it's helping your gut health, upping your protein-intake, restoring energy levels or eating lower-calorie meals, these unapologetically tasty, hassle-free recipes are guaranteed to deliver. From brunches and quick eats, puds and pick-me-ups, this is a book for anyone who cares about what goes into their bodies and what food can do to their mood and energy. It's for anyone looking to stick to a plant-based diet, or for plant-based eaters looking for healthy inspiration.
Introduction -- Brunch -- Quick eats -- Proper eats -- Puds -- Snacks -- Pick-me-ups -- Meal planners.
Includes index.
Keywords: Vegan cooking; Cooking (Natural foods); Cookbooks